Media and Old Age: Health Information-Seeking among Elderly Slum Dwellers in Kenya - Geoffrey Gathii Njenga; Mogambi, Hezron; Silas Oriaso (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: Investigating health information-seeking behavior among elderly slum dwellers empowers them with vital knowledge, enabling informed decisions and timely healthcare access. Understanding their unique information-seeking patterns aids in tailoring public communication campaigns, ultimately enhancing a healthier and more resilient community. In the Kibera slum, the elderly face a dearth of health information owing to their low socioeconomic status. Limited access to resources, including accessibility to various health information sources, exacerbates their informational gap. This hinders their ability to make informed decisions, potentially leading to delayed or inadequate healthcare, further compromising their well-being. The study presents ﬁndings on patterns of media use and health information seeking among the elderly in one of Africa’s biggest slums, Kibera. Patterns of media usage for health information among elderly slum dwellers based on age group, income, education level, and geographical location were investigated. Aims: This study's primary objective was to assess media use patterns for health information among elderly slum dwellers. Method: Interviews, focus group discussions, and key informant interviews targeting the elderly living in the Kibera slum were conducted. Qualitative findings identified Radio, Phone calls, WhatsApp, SMS, Email, Video calls, Television, Online Radio, Online Television, Facebook, Twitter, and Websites as health information sources across different demographic backgrounds. Results: These channels empowered elderly slum dwellers with knowledge, promoting positive lifestyle changes such as healthy eating. Conclusion: Recommendations to enhance these media channels include tailoring radio broadcasts to address the specific health concerns of older adults, innovative interpersonal communication approaches, and user-centered online media design which enhances accessibility. Conclusion: These results provide significant findings on media usage patterns for health information among elderly slum dwellers from different demographic backgrounds. The study identifies media usage patterns for health information, the types of health information sought from these channels, the behaviors promoted by these sources, and provides recommendations on how to improve these media channels.